The multidisciplinary study of selected fishing communities along Guimaras Strait fisheries module - Seraspe, Ebonia
Fish landings of three coastal baranggays are samples for two days at roughly five or six day intervals within each month from December 1981 to September 1982. The baranggays are Lanas, Barotac Nuevo and Banuyao, Miag-ao in Iloilo Province and Lusaran. Nueva Valencia in Guimaras Subprovince. Catches of different classes of boat in terms of type of gear used are sampled and analyzed based on species composition by weight and number. Of the catch, Lusaran has the highest with 751 tons; the catch is dominated by nemipterid species. This is followed by Lanas with 412 tons, 68% of which is shared by Leiognathus elongatus. Banuyao has the lowest with only 64 tons and is composed mostly of Sardinella fimbriata especially during December to April. Biological study of the dominant species reveals that after a year, N. nematophorus attains a size of at least 120 mm standard length at an average rate of growth of 10.0 mm per month; for S. fimbriata, a size of 64 mm standard length at an average rate of growth of 5.3 mm per month and for L. elongatus, a minimum standard length of 60 mm with an average growth rate of 5.0 mm per month. Of the six gonad maturity stages, S. fimbriata exhibits up to Stage V, while N. nematophorus and L. elongatus exhibit Stages 1 to IV only. Length at first maturity is attained at a standard length of 120 mm (140 mm total length) for S. fimbriata, 60 mm (74 mm total lenth) for L. elongatus and 100 mm (136 mm total length) for N. nematophorus. Fecundity in S. fimbriata ranges from 4,690 to 47, 196, in N. nematophorus 4, 162 to 36,880 and 1, 929 to 5,049 in L. elongatus. Copepods constitute the primary food item in the stomach of the species studied. All the three species are carnivorous. N. nematophorus is definitely a predator while S. fimbriata is a particulate feeder. L. elongatus, though a plankton feeder could resort to bottom feeding as well.
PCARRD Funded Research. -- Iloilo City : UPV-CAS, [1982].